Fibrous concentrate on the productive and reproductive performance of guinea pigs in family -commercial breeding in the Andes - Huanca, Bernardo Roque; Higuera, Miguel Alan Churata; Machaca, Regina Sumari; Aruquipa, José Eduardo Ramírez; Betancur, Heber Nehemias Chui (Revista de Ciências Agroveterinárias, 2024)
Andean guinea pig traditionally fed with forages presents low productive and reproductive performance. The aim of this study was to evaluate the effects of fibrous concentrate on the reproductive and productive performance of guinea pigs. A sample of 110 female guinea pigs (963.1 ± 127.3 g) and 22 male guinea pigs (1209.9 ± 159.0 g) of the Peru breed was distributed in 22 breeding modules (1 male/5 females), of which 11 modules were fed with forage (control) and 11 modules with fibrous concentrate (experimental). Each module was a replication. The forage was whole oat hay, while the fibrous concentrate was a mixture made with chopped hay from the same oats, corn-soybean, vitamin-mineral supplement, common salt, and premix. Both groups received the same amounts of fresh alfalfa as a vitamin C source. Then, 92 young weaning cavies from the control group (248.8 ± 29.9 g) and 106 young cavies from the experimental group (350.5 ± 64.6 g) were fed with the same diets to evaluate their productive performance. The experimental group surpassed the control group in all the variables (p < 0.05): dry matter intake (81.2 ± 4.5 vs 77.9 ± 1.0 g/day), postpartum female weight (1394.0 ± 81.5 vs. 1161.4 ± 50.3 g), male weight (1479.8 ± 125.1 vs. 1287.6 ± 124.4), litter size (2.24 ± 0.45 vs. 1.89 ± 0.68), litter weight (415.1 ± 80.2 vs. 291.3 ± 37.8 g), weaning weight (350.5 ± 64.6 vs. 248.8 ± 29.9 g), weight gain at 60 days of rearing (9.59 ± 1.41 vs. 6.41 ± 0.69 g), and rearing time to commercial weight (60 vs. 105 days), respectively. The fibrous concentrate achieves better reproductive and productive performance than forage and may be a viable alternative for family-commercial breeding of guinea pigs in the Andes.